Microencapsulation of Green Capulaga (Elettaria cardamomum) Essential Oil with Maltodextrin and Its Applications in Coffee Drink - Maria Erna Kustyawati; Ribut Sugiharto; Rini Rini (The University of Lampung, 2022)
Microencapsulation of green cardamom (Elettaria cardamomum) essential oils and its application is considered an innovative technique to improve the functional properties of coffee drinks. This study aims to determine the best formulations (M) of combination of maltodextrin and cardamom essential oil, parameters such as microcapsule yields, water content, and solubility were measured. To find out whether the microcapsule was applicable for coffee drink, antioxidant activity and taste and aroma of coffee drink mixed with the best formulation were analyzed. Completely Randomized Block Design (CRBD) with four replications was used; the data were analyzed by ANOVA and further tested by the LSD test with a level of 5%. The results showed that formulations significantly affected the yields and solubility of cardamom essential oil microcapsules. The best formulation treatment was formulation M3 with a yield score,water content and solubility of 89.03%, 11.85%, and 93.50%, respectively. Antioxidant activity, aroma and taste scores of ground coffee mixed with M3 were 77.61±0.23%, 4.31 (typical of cardamom, little coffee), and 4.88 (typical of cardamom, little coffee), respectively. While ground coffee only has antioxidant activity of 76.32±0.31%. In conclusion, ground coffee mixed with microencapsulated cardamom essential oil has the potential as a herbal coffee drink. Keywords: Cardamom, Essential oil, Herbal coffee drink, Microencapsulation